Honorarium Notary for Legal Services in Making Authentic Deed - Fonaha Hulu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to analyze the Notary's honorarium for legal services in making authentic deeds. Notary is one of the professions in the legal field, which provides legal services for citizens in terms of making authentic deeds. Every authentic deed made, of course, a notary as a legal service provider is entitled to receive an honorarium. This research is a normative juridical study, with a descriptive approach. In this research, it is further studied regarding the Notary's honorarium for legal services in making authentic deeds. In accordance with the provisions in Article 36 paragraph (2) UUJN, Notary fees for legal services in making authentic deeds are based on the economic value and sociological value of the deed that has been drawn up. In Article 36 paragraph (3) of the JN Law, it is determined that the economic value is determined from the object of each deed. Thus, the Notary's honorarium is important for legal services as an authentic deed maker.